Faktor-faktor UMKM dalam Mengadopsi E-Market di Kabupaten Ogan Ilir - Dita Rahmawati; Darius Antoni; Kurniawan (Penerbit Goodwood, 2021)
Purpose: The purpose of this study is to identify critical factors influencing SMEs in Ogan Ilir to adopt e-Marketing, in order to develop a concept of e-Marketing adoption in the Ogan Ilir Regency. Research Methodology: The study employs a survey method to collect data from MSME actors and the Department of Industry, Trade, Cooperatives, and MSMEs in Ogan Ilir Regency. The initial conceptual model developed within the TOE framework using e-Market was validated and tested using SEM on survey data. Results: The findings indicate a positive correlation between perceived direct benefits, top management support, external pressure, perceived trust, and identified e-Market adoption. However, it was determined that perceived indirect benefits and organizational readiness were insignificant in relation to e-Market adoption. Limitations: Because this research was conducted using TOE theory, additional development in areas such as behavior and infrastructure is required. Additionally, this research focuses exclusively on MSMEs in Ogan Ilir Regency and requires additional data to ensure that this concept is well received. Contribution: This study significantly contributes to the field of e-Market research, both theoretically and practically. This study adds to the existing body of knowledge in the field of e-Market and technology adoption in MSMEs by expanding the TOE framework to study e-Market adoption, developing a validated conceptual model to investigate the critical determinants of e-Market adoption in MSMEs in the Ogan Ilir district, and (c) providing MSMEs with an effective approach to assist them in the evaluation and selection of technology.